2018
DOI: 10.1080/14763141.2018.1472798
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fatigue on decision-making in athletes: a systematic review

Abstract: A potential challenge associated with sports is that athletes must often perform the cognitive processing associated with decision-making (i.e., movement selection) when fatigued. The purpose of this systematic review was to summarise studies that have analysed the extent to which fatigue influences the effects of decision-making on lower extremity mechanics during execution of common sports manoeuvres. We specifically focused on mechanics associated with ACL injury risk. Reviewers searched the PubMed, SPORTDi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
0
16
0
1
Order By: Relevance
“…In addition, given the connection between physical performance and tiredness ( Van Cutsem et al, 2017 ), blue light exposure may indeed improve an athlete’s physical performance, reduce the risk of injury and help in staying focused. Regarding the influence of tiredness on decision making, there is one study that found decision making not to be influenced by fatigue and therefore not by tiredness ( Almonroeder et al, 2020 ). In case an athlete shows signs of tiredness on competition days, about 2 h of blue light exposure might help to reduce tiredness, which was the average time of the included studies ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the connection between physical performance and tiredness ( Van Cutsem et al, 2017 ), blue light exposure may indeed improve an athlete’s physical performance, reduce the risk of injury and help in staying focused. Regarding the influence of tiredness on decision making, there is one study that found decision making not to be influenced by fatigue and therefore not by tiredness ( Almonroeder et al, 2020 ). In case an athlete shows signs of tiredness on competition days, about 2 h of blue light exposure might help to reduce tiredness, which was the average time of the included studies ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to question whether a fatigue protocol until exhaustion [ 41 ] reflects sports-specific physiological loads [ 78 ]. For example, in soccer, landing after heading a ball or cutting to pass an opponent typically is not carried out by the player in a state of maximal exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic video analysis reported that 68% of anterior cruciate ligament injuries happened in the first half, and one-quarter of them in the first 15 min of a football match [29]. This is probably due to a potentially higher injury risk caused by muscle fatigue [30] and subsequent reduction in postural control [31]. The authors suggested that this was possibly due to the inadequate neuromuscular readiness of fresh, unfatigued players [29].…”
Section: Discussionmentioning
confidence: 99%